Preparation method and application of ternary pole piece with primary coating of lithium iron phosphate

By coating the surface of the positive electrode base foil of the ternary lithium battery with lithium iron phosphate slurry and ternary material slurry to form a multi-layer structure, combined with improved conductivity and nano-scale coating layer, the thermal stability and cycle life problems of the ternary lithium battery are solved, and the safety and energy density of the battery at high temperature are improved.

CN120749115APending Publication Date: 2025-10-03JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511000839.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Ternary lithium batteries have poor thermal stability, are prone to thermal runaway at high temperatures, have a short cycle life, require a complex thermal management system, and are prone to side reactions with the electrolyte in high-temperature environments, resulting in increased interfacial impedance and accelerated capacity decay.

Method used

Lithium iron phosphate slurry and ternary material slurry are coated on the surface of the positive electrode base foil to form a multi-layer active material layer. The high structural stability and conductivity of the lithium iron phosphate layer are improved, and a nano-scale coating layer is formed by combining bio-based carbon sources and sol-gel method to inhibit side reactions and reduce interfacial impedance. Carbon nanotubes treated with mixed acid are used to enhance conductivity and porosity.

Benefits of technology

It improves the safety and electrochemical performance of the battery, extends the cycle life, enhances the battery safety and energy density at high temperatures, reduces the interface impedance, and improves the capacity retention rate of the battery at high and low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120749115A_ABST
    Figure CN120749115A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a ternary pole piece with a base coat of lithium iron phosphate, and relates to the technical field of battery materials. The lithium iron phosphate slurry and the ternary material slurry are coated on the surface of the positive electrode base foil, so that the safety and the electrochemical performance of the pole piece are improved. The lithium iron phosphate and the ternary material are used as active materials, an active substance layer is formed on the surface of the positive electrode base foil, the lithium iron phosphate has a stable olivine structure, the structure is not easy to collapse and decompose at a high temperature, the lithium iron phosphate is coated on the surface of the ternary material, a protective layer with high thermal stability is constructed, heat is prevented from being quickly transferred into the ternary material, and the thermal stability of the ternary material is improved. The structure change of the ternary material at high temperature is delayed; the ternary material is heated to expand in the charging and discharging process, the lithium iron phosphate priming coat has certain elasticity and buffering performance, stress generated in the thermal expansion process of the ternary material can be absorbed and dispersed, and structural damage caused by thermal expansion is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a preparation method of a ternary electrode sheet coated with lithium iron phosphate and an application thereof. Background Art

[0002] With the rapid development of new energy vehicles and electronic devices, the demand for lithium-ion batteries continues to increase. Ternary batteries, commonly referred to as ternary lithium batteries such as NCM (nickel-cobalt-manganese) and NCA (nickel-cobalt-aluminum), are widely used in new energy vehicles and consumer electronics. Their high energy density and excellent low-temperature performance make them an ideal choice for long-range electric vehicles and consumer electronics. However, safety and cost issues have limited their wider application.

[0003] In the prior art, the thermal stability of ternary lithium batteries is poor, and thermal runaway is prone to occur at high temperatures, posing a risk of fire. Compared with lithium iron phosphate, ternary lithium batteries have a shorter cycle life and faster capacity decay. A complex thermal management system is required to ensure that the battery operates at an appropriate temperature. In a high-temperature environment, its surface is prone to side reactions with the electrolyte, resulting in increased interfacial impedance and accelerated capacity decay. Therefore, the present invention provides a preparation method for a ternary electrode coated with lithium iron phosphate and its application to solve the above technical problems. Summary of the Invention

[0004] The purpose of the present invention is to provide a preparation method of a ternary electrode with a lithium iron phosphate primer and its application, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A ternary electrode sheet with a lithium iron phosphate (LFP) bottom coating includes a positive electrode base foil and an active material layer arranged on the surface of the positive electrode base foil; the active material layer is a lithium iron phosphate layer and a ternary material layer; the lithium iron phosphate layer is located between the positive electrode base foil and the ternary material layer.

[0006] Furthermore, the active material layer is multi-layered, and the lithium iron phosphate layer and the ternary material layer are arranged alternately.

[0007] A method for preparing a ternary electrode with a lithium iron phosphate primer coating comprises the following steps: S1: Mix PVDF (polyvinylidene fluoride), lithium iron phosphate, a conductive agent, and NMP (N-methylpyrrolidone) to obtain lithium iron phosphate slurry; S2: mixing PVDF, NMP, ternary material, and conductive agent to obtain ternary material slurry; S3: coating the surface of the positive electrode base foil with lithium iron phosphate slurry by gravure coating, drying, and rolling to form a lithium iron phosphate layer, and then coating the lithium iron phosphate layer with ternary material slurry by extrusion coating, drying, and rolling to form a ternary material layer to obtain an active material layer; S4: Repeat steps S3 0 to 5 times to obtain a ternary electrode.

[0008] Furthermore, the lithium iron phosphate slurry is specifically prepared by the following process: PVDF is added to NMP to fully dissolve, stirred, and added to a stirring tank, and then lithium iron phosphate and a conductive agent are added in batches, dispersed, and the solid content and viscosity of the slurry are adjusted to obtain lithium iron phosphate slurry.

[0009] Furthermore, the ternary material slurry is specifically prepared by the following process: PVDF is added to NMP to fully dissolve, stirred, and added to a stirring tank, and then the ternary material and conductive agent are added in batches in sequence, dispersed, and the solid content and viscosity of the slurry are adjusted to obtain the ternary material slurry.

[0010] Furthermore, the specific process for adjusting the solid content and viscosity of the slurry is as follows: adding solvent NMP to adjust the solid content of the slurry to 40-50%, and adjusting the viscosity of the slurry to 3000-5000 mPa·s.

[0011] Furthermore, in step S3, the drying process conditions are: drying at a temperature of 80-100° C. for 2-3 hours.

[0012] Furthermore, the stirring process conditions are: stirring at a rotation speed of 23-27 r / min for 3-60 min; the dispersion process conditions are: dispersing at a rotation speed of 2300-2500 r / min for 3-60 min.

[0013] Furthermore, the thickness of the lithium iron phosphate layer is 2-5 μm.

[0014] Furthermore, the thickness of the ternary material layer is 3 to 7 times the thickness of the lithium iron phosphate layer.

[0015] In the above technical solution, LFP has excellent thermal stability. Its olivine structure and stable PO bonds make it difficult to decompose at high temperatures. It can effectively prevent thermal runaway of the battery under high temperature conditions, prevent the shrinkage of the diaphragm at high temperatures, and maintain the integrity of the diaphragm at high temperatures, thereby improving the safety of the battery; the voltage platform of LFP is low and stable, and is located within the electrochemical stability window of the existing electrolyte, which can effectively prevent the decomposition of the electrolyte. After LFP is coated on the bottom of the positive electrode base foil, a protective layer can be formed to reduce the direct contact between the electrolyte and the ternary positive electrode material, thereby reducing the risk of decomposition of the electrolyte under high temperature or overcharge conditions; the LFP coating can inhibit the side reactions that may occur in the ternary material during the charging and discharging process; the crystal structure of LFP has little volume change and low internal stress during the charging and discharging process, which makes its structure more stable during the cycle.

[0016] Furthermore, the mass ratio of PVDF, lithium iron phosphate, and conductive agent is (3~6): (85~95): (2~8).

[0017] Furthermore, the mass ratio of PVDF, ternary material, and conductive agent is (3~6): (85~95): (2~8).

[0018] Furthermore, the ternary material is 622 type NCM (nickel cobalt manganese).

[0019] Furthermore, the conductive agent is a mixture of any one or more of conductive carbon black, carbon fiber, and carbon nanotubes.

[0020] Furthermore, the positive electrode base foil is aluminum foil.

[0021] Furthermore, the lithium iron phosphate is surface-modified, and the modification process is as follows: Step 1: Mix lithium iron phosphate and a bio-based carbon source, add deionized water, and perform ultrasonic dispersion to obtain a mixed slurry; Step 2: heat-treating the mixed slurry to obtain carbon-coated lithium iron phosphate; Step 3: adding soluble aluminum salt to deionized water to dissolve, adjusting the pH, and obtaining an aluminum source sol; Step 4: Immerse the carbon layer-coated lithium iron phosphate in aluminum source sol, stir, and after the reaction is completed, heat treat to obtain modified lithium iron phosphate.

[0022] In the above technical solution, the bio-based carbon source is uniformly attached to the surface of lithium iron phosphate (LiFePO4) particles under ultrasonic dispersion and then undergoes carbon thermal reduction reaction after heat treatment to generate an amorphous carbon layer with good conductivity, which not only improves the conductivity as an electron transmission channel, but also inhibits the Fe 2+ Oxidized to Fe 3+ , maintaining the stability of the olivine structure; soluble aluminum salt reacts with phosphoric acid to form a sol, and after impregnation, a nano-scale coating layer is formed on the surface of the carbon layer through the sol-gel method. Heat treatment causes aluminum ions to partially dope into the LiFePO4 lattice, forming LiFe1- x Al x PO4 (aluminum-doped lithium iron phosphate) solid solution, while forming a C-AlPO4 (aluminum phosphate carbon) heterogeneous interface with the carbon layer, inhibiting the side reaction between lithium iron phosphate and the electrolyte. The double-coating structure reduces the interface impedance and improves the capacity retention rate at high and low temperatures.

[0023] Furthermore, the bio-based carbon source is a mixture of any one or more of sucrose, glucose, fructose, starch, microcrystalline cellulose, and lignin sulfonate.

[0024] Furthermore, the soluble aluminum salt is a mixture of any one or more of aluminum sulfate and aluminum nitrate.

[0025] Furthermore, the mass ratio of lithium iron phosphate, bio-based carbon source, and deionized water is 10:1:(40~50).

[0026] Furthermore, the mass ratio of the soluble aluminum salt to the deionized water is 1:(50~80).

[0027] Furthermore, the mass ratio of the carbon layer-coated lithium iron phosphate to the aluminum source sol is (3-4):1.

[0028] Furthermore, in step 1, the process conditions for ultrasonic dispersion are: at a temperature of 60-80° C., a power of 1-1.5 kW, and a time of 30-40 min.

[0029] Furthermore, in step 2, the process conditions of the heat treatment are: heating to 500-700° C. at a heating rate of 2-5° C. / min and keeping warm for 2-4 hours.

[0030] Furthermore, in step three, the process conditions for adjusting the pH are: using a phosphoric acid solution with a concentration of 1-5 wt % and adjusting the pH to 3.5-5.

[0031] Furthermore, in step 4, the process conditions of the heat treatment are: heating to 500-700°C, keeping warm for 2-3 hours, and cooling to room temperature.

[0032] Furthermore, the conductive agent is a composite carbon nanotube, which is prepared by the following process: Step 1: mixing carbon nanotubes with mixed acid, filtering and drying after the reaction is completed to obtain carboxylated carbon nanotubes; Step 2: Mix the carboxylated carbon nanotubes with the sulfur compound, add a catalyst, add a solvent, and perform microwave reaction. After the reaction is completed, filter, wash, and dry to obtain composite carbon nanotubes.

[0033] Furthermore, the mass ratio of carbon nanotubes to mixed acid is 1:(30-40).

[0034] Furthermore, the mass ratio of the carboxylated carbon nanotubes, the sulfur source compound, the catalyst, and the solvent is 1:1:0.5:(40-50).

[0035] Furthermore, the mixed acid is a mixture of sulfuric acid and nitric acid, the volume ratio of sulfuric acid to nitric acid is (3-4):1, the concentration of sulfuric acid is 80-90wt%, and the concentration of nitric acid is 60-70wt%.

[0036] Furthermore, the sulfur source compound is any one of thiourea, thioacetamide, and sodium polysulfide.

[0037] Furthermore, the catalyst is stannous octoate.

[0038] Furthermore, the solvent is DMF (dimethylformamide).

[0039] Furthermore, in step 1, the drying process conditions are: drying at a temperature of 60-70° C. for 2-3 hours.

[0040] Furthermore, in step 2, the process conditions of the microwave reaction are: at a temperature of 120-180° C., a power of 300-800 W, and a reaction time of 5-30 min.

[0041] In the above technical effects, carboxyl polar functional groups are introduced on the surface of carbon nanotubes by acidification treatment with mixed acid, and then combined with carboxylated carbon nanotubes through microwave reaction to form a sulfur-doped structure. The introduction of sulfur element enhances the electrochemical performance of the electrode; stannous octoate is a Lewis acid catalyst to promote the decarboxylation reaction of carboxyl groups. Tin ions coordinate with carboxyl oxygen atoms, causing the carboxyl groups to remove CO2 to generate surface active sites. The sulfur source compound decomposes sulfur free radicals under heating conditions. The sulfur free radicals (S - ) is embedded into the surface of carbon nanotubes through covalent bonding to form composite carbon nanotubes containing sulfur compounds, which increases the specific surface area and porosity of carbon nanotubes and the number of ion storage active sites, thereby improving rate performance and increasing energy density; sulfur atoms can introduce additional π electron delocalization, improve conductivity, and stable chemical bonding can inhibit structural collapse during the cycle, alleviate the volume expansion of carbon nanotubes, and extend the cycle life.

[0042] An application of a ternary electrode with a lithium iron phosphate primer coating includes the following steps: Step (1): using the obtained ternary electrode sheet coated with lithium iron phosphate as the positive electrode sheet, taking the negative electrode sheet and the separator, adopting the lamination process, hot pressing, and obtaining a battery cell; Step (2): Place the laminated battery cell into an aluminum-plastic film shell, seal it by heat sealing process, inject electrolyte, and obtain a fully assembled battery after formation.

[0043] Furthermore, the hot pressing process conditions are: at a temperature of 75-110°C, in a nitrogen atmosphere with a flow rate of 3-7 L / min, hot pressing for 10-15 seconds. Compared with the prior art, the present invention has the following beneficial effects: 1. The lithium iron phosphate-based ternary electrode of the present invention improves the safety and electrochemical performance of the electrode by coating the surface of the positive electrode base foil with lithium iron phosphate slurry and ternary material slurry.

[0044] 2. The present invention provides a ternary electrode with a lithium iron phosphate bottom coating. The interior of the ternary electrode is composed of lithium iron phosphate layers and ternary material layers arranged alternately. The high structural stability of the lithium iron phosphate layer inhibits the crack propagation caused by volume expansion of the ternary material during the cycle, reduces the dissolution of transition metals, and thus extends the battery cycle life.

[0045] 3. The present invention relates to a ternary electrode with a lithium iron phosphate primer, which improves the conductivity and maintains the stability of the lithium iron phosphate olivine structure by using a bio-based carbon source to generate an amorphous carbon layer with good conductivity; a nano-scale coating layer is formed on the surface of the carbon layer by a sol-gel method, which promotes the partial doping of aluminum ions into the LiFePO4 lattice to form LiFe1- x Al x PO4 (aluminum-doped lithium iron phosphate) solid solution, while forming a C-AlPO4 (aluminum phosphate carbon) heterogeneous interface with the carbon layer, inhibiting the side reaction between lithium iron phosphate and the electrolyte. The double-coating structure reduces the interface impedance and improves the capacity retention rate at high and low temperatures.

[0046] 4. The present invention provides a ternary electrode with a lithium iron phosphate primer coating. By acidifying carbon nanotubes with mixed acid, carboxyl polar functional groups are introduced on the surface. The carbon nanotubes are combined with the carboxylated carbon nanotubes through microwave reaction to form a sulfur-doped structure, thereby enhancing the electrochemical performance of the electrode, increasing the specific surface area and porosity of the carbon nanotubes, and increasing the number of ion storage active sites, thereby improving rate performance and increasing energy density. Sulfur atoms can introduce additional π electron delocalization to improve conductivity, and the stable chemical bonding can inhibit structural collapse during the cycle, alleviate the volume expansion of the carbon nanotubes, and extend the cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Schematic diagram of the structure of the ternary electrode; Figure: 101 is the positive electrode base foil, 102 is the lithium iron phosphate layer, and 103 is the ternary material layer. DETAILED DESCRIPTION

[0048] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0049] In the following specific embodiments, like Figure 1 As shown, 101 is a positive electrode base foil, 102 is a lithium iron phosphate layer, and 103 is a ternary material layer; The battery uses a small soft-pack battery with a negative electrode of pure graphite and a nominal capacity of 3.1Ah. PVDF (polyvinylidene fluoride), model HSV900; The mass ratio of PVDF, lithium iron phosphate, and conductive agent is 3:85:2; The mass ratio of PVDF, ternary material, and conductive agent is 3:85:2; PVDF accounts for 10% of the mass of NMP (N-methylpyrrolidone); The thickness of the lithium iron phosphate layer is 2 μm; Carbon nanotubes, model GT-300, purity 97.5%; Ternary material, model 622 NCM (nickel cobalt manganese); Positive electrode base foil 101, aluminum foil, average thickness of 10 μm; The electrolyte is LiPF6 (lithium hexafluorophosphate) as the solute and EC / DMC (ethylene carbonate / dimethyl carbonate) as the solvent. The electrolyte concentration is 1 mol / L and the volume ratio of EC to DMC is 1:1. Example

[0050] A method for preparing a ternary electrode with a lithium iron phosphate primer coating comprises the following steps: S1: PVDF was added to NMP (N-methylpyrrolidone) to fully dissolve, stirred at a speed of 23 r / min for 10 min, and added to a stirring tank. Lithium iron phosphate and carbon nanotubes were then added twice, each half by weight, and dispersed at a speed of 2300 r / min for 10 min to obtain lithium iron phosphate slurry; S2: PVDF was added to NMP to fully dissolve, stirred at a speed of 23 r / min for 10 min, and added to a stirring tank. Then, the ternary material and carbon nanotubes were added twice, and dispersed at a speed of 2300 r / min for 10 min to obtain a ternary material slurry; S3: Lithium iron phosphate slurry was coated on the surface of the positive electrode base foil by gravure coating, dried at 80°C for 2 hours, and rolled to form a lithium iron phosphate layer. Then, ternary material slurry was coated on the lithium iron phosphate layer by extrusion coating, dried at 80°C for 2 hours, and rolled to form a ternary material layer. The compacted density was 3.5 g / cm 3 The ternary electrode.

[0051] Example 2: A method for preparing a ternary electrode with a lithium iron phosphate primer coating comprises the following steps: S1: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 20 min, and added to a stirring tank. Lithium iron phosphate and carbon nanotubes were then added twice, each half by weight, and dispersed at a speed of 2400 r / min for 20 min to obtain lithium iron phosphate slurry; S2: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 20 min, and added to a stirring tank. Then, the ternary material and carbon nanotubes were added twice, and dispersed at a speed of 2400 r / min for 20 min to obtain a ternary material slurry; S3: coating the surface of the positive electrode base foil with lithium iron phosphate slurry by gravure coating, drying at 90°C for 2.5 hours, and rolling to form a lithium iron phosphate layer, and then coating the lithium iron phosphate layer with ternary material slurry by extrusion coating, drying at 90°C for 2.5 hours, and rolling to form a ternary material layer to obtain an active material layer; S4: Repeat step S3 twice to obtain a compacted density of 3.5 g / cm 3 The ternary electrode.

[0052] Example 3: A method for preparing a ternary electrode with a lithium iron phosphate primer coating comprises the following steps: S1: PVDF was added to NMP to fully dissolve, stirred at a speed of 27 r / min for 60 min, and added to a stirring tank. Lithium iron phosphate and carbon nanotubes were then added twice, each half by weight, and dispersed at a speed of 2500 r / min for 60 min to obtain a lithium iron phosphate slurry; S2: PVDF was added to NMP to fully dissolve, stirred at a speed of 27 r / min for 60 min, and added to a stirring tank. The ternary material and carbon nanotubes were then added twice, and dispersed at a speed of 2500 r / min for 60 min to obtain a ternary material slurry; S3: coating the surface of the positive electrode base foil with lithium iron phosphate slurry by gravure coating, drying at 100°C for 3 hours, and rolling to form a lithium iron phosphate layer, and then coating the lithium iron phosphate layer with ternary material slurry by extrusion coating, drying at 100°C for 3 hours, and rolling to form a ternary material layer to obtain an active material layer; S4: Repeat step S3 4 times to obtain a compacted density of 3.5 g / cm 3 The ternary electrode.

[0053] Example 4: A method for preparing a ternary electrode with a lithium iron phosphate primer coating comprises the following steps: S1: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 30 min, and added to a stirring tank. Lithium iron phosphate and carbon nanotubes were then added twice, each half by weight, and dispersed at a speed of 2400 r / min for 30 min to obtain lithium iron phosphate slurry; S2: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 30 min, and added to a stirring tank. Then, the ternary material and carbon nanotubes were added twice, and dispersed at a speed of 2400 r / min for 30 min to obtain a ternary material slurry; S3: coating the surface of the positive electrode base foil with lithium iron phosphate slurry by gravure coating, drying at 90°C for 2.5 hours, and rolling to form a lithium iron phosphate layer, and then coating the lithium iron phosphate layer with ternary material slurry by extrusion coating, drying at 90°C for 2.5 hours, and rolling to form a ternary material layer to obtain an active material layer; S4: Repeat step S3 4 times to obtain a compacted density of 3.5 g / cm 3 The ternary electrode.

[0054] The lithium iron phosphate is surface-modified, and the modification process is as follows: Step 1: Mix lithium iron phosphate and a bio-based carbon source, add deionized water, and heat at 60°C, 1 kW power, and 30 minutes to obtain a mixed slurry; the mass ratio of lithium iron phosphate, bio-based carbon source, and deionized water is 10:1:40; Step 2: heating the mixed slurry to 500°C at a heating rate of 2°C / min and keeping the temperature for 2 hours to obtain carbon-coated lithium iron phosphate; Step 3: dissolving a soluble aluminum salt in deionized water, adjusting the pH to 3.5 using a 1 wt % phosphoric acid solution, to obtain an aluminum source sol; the mass ratio of the soluble aluminum salt to the deionized water is 1:50; Step 4: Immerse the carbon-coated lithium iron phosphate in the aluminum source sol. After the reaction is completed, heat to 500°C, keep warm for 2 hours, and cool to room temperature to obtain modified lithium iron phosphate; the mass ratio of the carbon-coated lithium iron phosphate to the aluminum source sol is 3:1.

[0055] The conductive agent is a composite carbon nanotube, which is made by the following process: Step 1: mixing carbon nanotubes with mixed acid, filtering after the reaction, and drying at 60°C for 2 hours to obtain carboxylated carbon nanotubes; the mass ratio of carbon nanotubes to mixed acid is 1:30; Step 2: Mix the carboxylated carbon nanotubes with the sulfur source compound, add a catalyst, and add a solvent. The process conditions of the microwave reaction are: at a temperature of 120°C, a power of 300W, and a reaction time of 5 minutes. After the reaction is completed, filter and wash, and dry at a temperature of 60°C for 2 hours to obtain composite carbon nanotubes; the mass ratio of the carboxylated carbon nanotubes, the sulfur source compound, the catalyst, and the solvent is 1:1:0.5:40.

[0056] Example 5: A method for preparing a ternary electrode with a lithium iron phosphate primer coating comprises the following steps: S1: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 30 min, and added to a stirring tank. Lithium iron phosphate and carbon nanotubes were then added twice, each half by weight, and dispersed at a speed of 2400 r / min for 30 min to obtain lithium iron phosphate slurry; S2: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 30 min, and added to a stirring tank. Then, the ternary material and carbon nanotubes were added twice, and dispersed at a speed of 2400 r / min for 30 min to obtain a ternary material slurry; S3: coating the surface of the positive electrode base foil with lithium iron phosphate slurry by gravure coating, drying at 90°C for 2.5 hours, and rolling to form a lithium iron phosphate layer, and then coating the lithium iron phosphate layer with ternary material slurry by extrusion coating, drying at 90°C for 2.5 hours, and rolling to form a ternary material layer to obtain an active material layer; S4: Repeat step S3 4 times to obtain a compacted density of 3.5 g / cm 3 The ternary electrode.

[0057] The lithium iron phosphate is surface-modified, and the modification process is as follows: Step 1: Mix lithium iron phosphate and a bio-based carbon source, add deionized water, and heat at 80°C, 1.5 kW, and 40 minutes to obtain a mixed slurry; the mass ratio of lithium iron phosphate, bio-based carbon source, and deionized water is 10:1:50; Step 2: heating the mixed slurry to 700°C at a heating rate of 5°C / min and keeping the temperature for 4 hours to obtain carbon-coated lithium iron phosphate; Step 3: dissolving a soluble aluminum salt in deionized water, adjusting the pH to 5 using a 5 wt % phosphoric acid solution, and obtaining an aluminum source sol; the mass ratio of the soluble aluminum salt to the deionized water is 1:80; Step 4: Immerse the carbon-coated lithium iron phosphate in the aluminum source sol. After the reaction is completed, heat to 700°C, keep warm for 3 hours, and cool to room temperature to obtain modified lithium iron phosphate; the mass ratio of the carbon-coated lithium iron phosphate to the aluminum source sol is 4:1.

[0058] The conductive agent is a composite carbon nanotube, which is made by the following process: Step 1: mixing carbon nanotubes with mixed acid, filtering after the reaction, and drying at 70°C for 3 hours to obtain carboxylated carbon nanotubes; the mass ratio of carbon nanotubes to mixed acid is 1:40; Step 2: Mix the carboxylated carbon nanotubes with the sulfur source compound, add a catalyst, and add a solvent. The process conditions of the microwave reaction are: at a temperature of 180°C, a power of 800W, and a reaction time of 30 minutes. After the reaction is completed, filter and wash, and dry at a temperature of 70°C for 3 hours to obtain composite carbon nanotubes; the mass ratio of the carboxylated carbon nanotubes, the sulfur source compound, the catalyst, and the solvent is 1:1:0.5:50.

[0059] Example 6: A method for preparing a ternary electrode with a lithium iron phosphate primer coating comprises the following steps: S1: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 30 min, and added to a stirring tank. Lithium iron phosphate and carbon nanotubes were then added twice, each half by weight, and dispersed at a speed of 2400 r / min for 30 min to obtain lithium iron phosphate slurry; S2: PVDF was added to NMP to fully dissolve, stirred at a speed of 25 r / min for 30 min, and added to a stirring tank. Then, the ternary material and carbon nanotubes were added twice, and dispersed at a speed of 2400 r / min for 30 min to obtain a ternary material slurry; S3: coating the surface of the positive electrode base foil with lithium iron phosphate slurry by gravure coating, drying at 90°C for 2.5 hours, and rolling to form a lithium iron phosphate layer, and then coating the lithium iron phosphate layer with ternary material slurry by extrusion coating, drying at 90°C for 2.5 hours, and rolling to form a ternary material layer to obtain an active material layer; S4: Repeat step S3 4 times to obtain a compacted density of 3.5 g / cm 3 The ternary electrode.

[0060] The lithium iron phosphate is surface-modified, and the modification process is as follows: Step 1: Mix lithium iron phosphate and a bio-based carbon source, add deionized water, and heat at 70°C, a power of 1.2 kW, and a time of 35 minutes to obtain a mixed slurry; the mass ratio of lithium iron phosphate, bio-based carbon source, and deionized water is 10:1:45; Step 2: heating the mixed slurry to 600°C at a heating rate of 3°C / min and keeping the temperature for 3 hours to obtain carbon-coated lithium iron phosphate; Step 3: Dissolve the soluble aluminum salt in deionized water, adjust the pH to 4 using a 3 wt % phosphoric acid solution, and obtain an aluminum source sol; the mass ratio of the soluble aluminum salt to the deionized water is 1:70; Step 4: Immerse the carbon-coated lithium iron phosphate in the aluminum source sol. After the reaction is completed, heat to 600°C, keep warm for 2.5 hours, and cool to room temperature to obtain modified lithium iron phosphate; the mass ratio of the carbon-coated lithium iron phosphate to the aluminum source sol is 3.5:1.

[0061] The conductive agent is a composite carbon nanotube, which is made by the following process: Step 1: mixing carbon nanotubes with mixed acid, filtering after the reaction, and drying at 70°C for 3 hours to obtain carboxylated carbon nanotubes; the mass ratio of carbon nanotubes to mixed acid is 1:35; Step 2: Mix the carboxylated carbon nanotubes with the sulfur source compound, add a catalyst, and add a solvent. The process conditions of the microwave reaction are: at a temperature of 180°C, a power of 800W, and a reaction time of 30 minutes. After the reaction is completed, filter and wash, and dry at a temperature of 70°C for 3 hours to obtain composite carbon nanotubes; the mass ratio of the carboxylated carbon nanotubes, the sulfur source compound, the catalyst, and the solvent is 1:1:0.5:45.

[0062] Comparative Example 1: This comparative example provides a method for preparing an electrode. The active material layer is a lithium iron phosphate layer, and the rest of the method is the same as that of Example 1.

[0063] Comparative Example 2: This comparative example provides a method for preparing an electrode, wherein the active material layer is a ternary material layer, and the rest of the method is the same as that of Example 1.

[0064] Comparative Example 3: This comparative example provides a method for preparing an electrode. The lithium iron phosphate in the active material layer is modified lithium iron phosphate, and the conductive agent is carbon nanotubes. The remaining methods are the same as those in Example 4.

[0065] Comparative Example 4: This comparative example provides a method for preparing an electrode. The active material layer is lithium iron phosphate, the conductive agent is composite carbon nanotubes, and the remaining methods are the same as those in Example 4.

[0066] experiment: The battery cells obtained in Examples 1-6 and Comparative Examples 1-4 were placed in an aluminum-plastic film shell, hot-pressed for 10 seconds at a temperature of 90°C and a nitrogen atmosphere at a flow rate of 5 L / min, sealed by a heat sealing process, injected with electrolyte, and formed to obtain fully assembled batteries. Samples were made, tested, and the results were recorded.

[0067] First efficiency test: Using GB / T 23365-2023 as the reference standard, use a battery program-controlled tester to test the battery charge and discharge rates, and calculate the ratio of the first discharge specific capacity to the first charge specific capacity to obtain the first efficiency.

[0068] DC internal resistance test: GB / T 31486-2015 is used as the reference standard. The pulse current method is used to instantly change the battery voltage through a large current pulse, and the internal resistance is calculated using Ohm's law.

[0069] Needle penetration test: Using GB / T 31485-2015 as the reference standard, use a φ5 mm high-temperature resistant steel needle (the cone angle of the needle tip is 45°, the needle surface is smooth, free of rust, oxide layer and oil), and penetrate the battery plate at a speed of 25 mm / s from a direction perpendicular to the battery plate. The penetration position should be close to the geometric center of the punctured surface. The steel needle stays in the battery. Observe for fire or explosion one hour after the needle penetration and record the test results.

[0070] Extrusion test: Using GB 31241-2014 as the reference standard, apply pressure perpendicular to the battery plate. Extrusion plate form: semi-cylinder with a radius of 75mm, and the length of the semi-cylinder (L) should be greater than the battery size. Extrusion speed: 5mm / s. Extrusion degree: Stop extrusion when the voltage reaches 0V, or the deformation reaches 30%, or the extrusion force reaches 200kN. Observe for 1 hour and record the test results.

[0071] Performance comparison table

[0072] According to the data in the above table, we can clearly draw the following conclusions: The ternary electrode pieces obtained in Examples 1-6 were compared with the ternary electrode pieces obtained in Comparative Examples 1-4. The test results show that: Compared with Comparative Example 2, the ternary electrodes obtained in Examples 1-6 have high initial efficiency, large DC internal resistance, and no explosion occurred in the needle penetration test and the extrusion test.

[0073] It can be seen from the test data of Examples 1-3 that the higher the proportion of ternary materials, the higher the first efficiency, the lower the DCR, the less energy loss during the first charge and discharge, and the higher the initial energy density of the battery.

[0074] It can be seen from the puncture and extrusion tests that with the introduction of the lithium iron phosphate primer layer in the active material layer and the increase in the number of layers, the safety of puncture and extrusion is improved.

[0075] After the lithium iron phosphate undercoat was introduced in Examples 1-6, the electrode plates did not explode during either the needle penetration or extrusion tests, demonstrating excellent safety performance. In Comparative Example 1, the active material layer was a lithium iron phosphate layer, which did not explode during either the needle penetration or extrusion tests. However, in Comparative Example 2, the active material layer was a ternary material layer, which exploded in both tests, demonstrating that the lithium iron phosphate undercoat effectively improves battery safety.

[0076] Since the ion diffusion system of LFP is lower than that of NCM, as the number of lithium iron phosphate layers increases, the first efficiency gradually decreases and the DCR increases, but the battery safety is relatively high.

[0077] In Examples 4, 5, and 6, composite carbon nanotubes were used as a conductive agent, and the lithium iron phosphate was surface-modified, further improving the electrochemical performance of the electrode. Comparative Examples 3 and 4, using carbon nanotubes and lithium iron phosphate, respectively, showed that their initial efficiency and DC internal resistance were inferior to those of Examples 4, 5, and 6, demonstrating that the dual modification of carbon nanotubes and lithium iron phosphate significantly improved the performance of the ternary electrode.

[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

Claims

1. A ternary electrode sheet coated with lithium iron phosphate, comprising a positive electrode base foil (101) and an active material layer arranged on the surface of the positive electrode base foil (101), characterized in that: The active material layer comprises a lithium iron phosphate layer (102) and a ternary material layer (103); the lithium iron phosphate layer (102) is located between the positive electrode base foil (101) and the ternary material layer (103); the active material layer is multi-layered, and the lithium iron phosphate layer (102) and the ternary material layer (103) are arranged alternately.

2. A method for preparing a ternary electrode with a lithium iron phosphate primer, characterized in that: The following steps are involved: S1: Mixing PVDF, lithium iron phosphate, a conductive agent, and NMP to obtain lithium iron phosphate slurry; S2: mixing PVDF, NMP, ternary material, and conductive agent to obtain ternary material slurry; S3: coating the surface of the positive electrode base foil (101) with lithium iron phosphate slurry by gravure coating, drying, and rolling to form a lithium iron phosphate layer (102), and then coating the lithium iron phosphate layer (102) with ternary material slurry by extrusion coating, drying, and rolling to form a ternary material layer (103), thereby obtaining an active material layer; S4: Repeat steps S3 0 to 5 times to obtain a ternary electrode.

3. The method for preparing a ternary electrode sheet with a lithium iron phosphate primer according to claim 2, characterized in that: Lithium iron phosphate slurry is specifically prepared by the following process: PVDF is added to NMP to fully dissolve, stirred, and added to a stirring tank, and then lithium iron phosphate and a conductive agent are added in batches, dispersed, and the solid content and viscosity of the slurry are adjusted to obtain lithium iron phosphate slurry; ternary material slurry is specifically prepared by the following process: PVDF is added to NMP to fully dissolve, stirred, and added to a stirring tank, and then ternary materials and a conductive agent are added in batches, dispersed, and the solid content and viscosity of the slurry are adjusted to obtain ternary material slurry.

4. The method for preparing a ternary electrode sheet with a lithium iron phosphate primer coating according to claim 2, characterized in that: The mass ratio of PVDF, lithium iron phosphate and conductive agent is (3~6) : (85~95) : (2~8); the mass ratio of PVDF, ternary material and conductive agent is (3~6) : (85~95) : (2~8).

5. The method for preparing a ternary electrode sheet with a lithium iron phosphate primer coating according to claim 2, characterized in that: The stirring process conditions are: stirring at a rotation speed of 23-27 r / min for 3-60 min; the dispersion process conditions are: dispersing at a rotation speed of 2300-2500 r / min for 3-60 min.

6. The method for preparing a ternary electrode sheet with a lithium iron phosphate primer coating according to claim 3, characterized in that: The lithium iron phosphate is surface-modified, and the modification process is as follows: Step 1: Mix lithium iron phosphate and a bio-based carbon source, add deionized water, and perform ultrasonic dispersion to obtain a mixed slurry; Step 2: heat-treating the mixed slurry to obtain carbon-coated lithium iron phosphate; Step 3: adding soluble aluminum salt to deionized water to dissolve, adjusting the pH, and obtaining an aluminum source sol; Step 4: Immerse the carbon layer-coated lithium iron phosphate in aluminum source sol, stir, and after the reaction is completed, heat treat to obtain modified lithium iron phosphate.

7. The method for preparing a ternary electrode sheet with a lithium iron phosphate primer coating according to claim 6, characterized in that: The bio-based carbon source is a mixture of any one or more of sucrose, glucose, fructose, starch, microcrystalline cellulose, and lignin sulfonate; and the soluble aluminum salt is a mixture of any one or more of aluminum sulfate and aluminum nitrate.

8. The method for preparing a ternary electrode sheet with a lithium iron phosphate primer coating according to claim 2, characterized in that: The conductive agent is a composite carbon nanotube, which is made by the following process: Step 1: mixing carbon nanotubes with mixed acid, filtering and drying after the reaction is completed to obtain carboxylated carbon nanotubes; Step 2: Mix the carboxylated carbon nanotubes with the sulfur source compound, add a catalyst, add a solvent, and perform microwave reaction. After the reaction is completed, filter, wash, and dry to obtain composite carbon nanotubes.

9. The method for preparing a ternary electrode sheet with a lithium iron phosphate primer coating according to claim 8, characterized in that: The sulfur source compound is any one of thiourea, thioacetamide, and sodium polysulfide; the catalyst is stannous octoate; and in step 2, the process conditions of the microwave reaction are: at a temperature of 120-180° C., a power of 300-800 W, and a reaction time of 5-30 min.

10. Application of a ternary electrode sheet with a lithium iron phosphate primer coating prepared by the preparation method according to any one of claims 1 to 9, characterized in that: Application in the preparation of battery materials.

Citation Information

Cited By

  • Composite positive pole piece, preparation method and application thereof and lithium ion battery

    CN121885534A